PENGARUH TEMPERATUR DAN WAKTU PEMANASAN ZEOLIT PELET TEKAN PADA AKTIVASI BASA-FISIK NaOH DAN KOH TERHADAP PRESTASI MOTOR DIESEL 4-LANGKAH - Novian Korin A; Herry Wardono (Jurnal Ilmiah Teknik Mesin, 2013)
Natural Zeolite is one of alternative adsorbents. Zeolite should be firstly activated to get zeolite with high adsorption capacity. The ability of chemical-physical activated zeolite in saving fuel consumption of a diesel engine proven by Herry Wardono using NaOH and KOH with normality of 0,75N. The mass of pressed pelletized zeolite used was 100 grams and with thermal activation at 200°C for 2 hour. In this research, zeolites were activated by using thermal activation at 150°C for 1 hour and 2 hours, and 200°C for 1 hour, these pellets were packed in a frame of 50 grams, 100 grams and 150 grams, and put them in the air filter of a diesel engine for each mass, so combustion air was firstly contacted with zeolites before entering to combustion chamber. The experiments were operated at engine speeds of 1500, 2000, 2500, 3000 rpm. The results showed that used of these thermal-Alkali activated zeolites could in increas the diesel engine performance. Use of 150 grams of KOH 0,75N activated zeolite that was thermally treated at 150oC for 2 hours could reduce the highest fuel consumption that was 0,0225 kg/kWh (11,211%), and as big as 0,0218 kg/kWh (10,87%) for use of 150 grams of NaOH 0,75N activated zeolite that was thermally treated at same condition. Meanwhile, the highest increase of brake power occurred for use of 100 grams of NaOH 0.75N activated zeolite that was 0,054 kW (7,667%), and as big as 0,0477 kW (6,849%) for use of 100 grams of KOH 0.75N activated zeolite. The results occurred at the engine speed of 1500 rpm.Keywords: thermal activation of Zeolite, Combustion air Treatment, Diesel Engine Performance